Biogas production from the landfilled easily degradable fraction of municipal solid waste: mining strategy for energy recovery - Torres Mayanga, Paulo César (2022)
The growing demand for space and fnancial resources to manage current and new municipal solid waste (MSW) landflls has become a massive challenge for several countries. Additionally, landflls contribute to adverse environmental impacts such as pollution and CO2 (carbon dioxide) and CH4 (methane) emissions. This paper has analyzed the possibility of producing biogas from landflled MSW. An easily degradable fraction of landflled MSW with 8 years of landflling was mined and subjected to chemical characterization and elemental composition analysis. The abbreviation for the study sample was called ED8 – Mined. The low values of lignin (24.5%) and nitrogen content (0.7%) and high values of holocellulose (75.9%) and C/N (46.1%) on dry basis were obtained resulting in materials with the potential to be used for biogas generation. Recal‑citrant materials were found in greater amounts than easily biodegradable fresh MSW fractions. The reuse of energy from landflled MSW can contribute positively to the country’s environment and economy, reducing environmental liabilities and generating energy in a controlled way. In Delta A Sanitary Landfll, Southeastern Brazil, the recovery of the ED8 – Mined would refect a signifcant recovery of about 100,000 tonnes of landflled materials for annual MSW cells of about 450,000 tonnes, allowing recovery of materials and space expansion for rejects.